2003
DOI: 10.1080/14786430310001607388
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modelling of nanomechanics and micromechanics: an overview

Abstract: Recent advances in analytical and computational modelling frameworks to describe the mechanics of materials on scales ranging from the atomistic, through the microstructure or transitional, and up to the continuum are reviewed. It is shown that multiscale modelling of materials approaches relies on a systematic reduction in the degrees of freedom on the natural length scales that can be identified in the material. Connections between such scales are currently achieved either by a parametrization or by a 'zoom-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 229 publications
1
67
0
1
Order By: Relevance
“…Due to the enormous difference in scales involved in correlating the macroscopic properties with the microscopic physical mechanisms of nanostructured materials, multiscale analysis is necessary (see, e.g., Shenoy et al, 1999;Curtin and Miller, 2003;Ghoniem et al, 2003). We adopt here a multiscale mechanics method to study the deformation and fracture behaviors of CNT-reinforced composites.…”
Section: Multiscale Mechanics Methods For Cnts In Compositesmentioning
confidence: 99%
“…Due to the enormous difference in scales involved in correlating the macroscopic properties with the microscopic physical mechanisms of nanostructured materials, multiscale analysis is necessary (see, e.g., Shenoy et al, 1999;Curtin and Miller, 2003;Ghoniem et al, 2003). We adopt here a multiscale mechanics method to study the deformation and fracture behaviors of CNT-reinforced composites.…”
Section: Multiscale Mechanics Methods For Cnts In Compositesmentioning
confidence: 99%
“…Computational studies of dislocation activity can be performed at several different length and time scales. In some cases, a multi-scale modeling approach is adopted (Ghoniem et al 2003). Core properties and atomic mechanisms are simulated using first principles calculations and molecular dynamics simulations.…”
Section: Molecular Dynamics Calculations Of Dislocation Defect Interamentioning
confidence: 99%
“…Dislocation motion is thought to be the main mechanism for deformation, because a fairly high density of network dislocations are generated during irradiation, and the dislocation sink strength for point defects is much higher that the grain boundary sink strength for point defects. Computational studies of dislocation activity can be performed at several different length and time scales (Ghoniem, Busso et al 2003) that are shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In recent time, multiscale modeling and computation have become powerful tool in solving many problems related to strongly coupled dynamics and multiphysics phenomena in material science and engineering [1,2]. Such an attempt, with judicious choice of the mathematical models which represent the mutually inseparable physical processes at the molecular scale, the lattice scale, the microstructural scale, and at the continuum scale, can be highly reliable in interpreting the experimental results and also in designing new materials and devices with desired multifunctionality.…”
Section: Introductionmentioning
confidence: 99%